Artritis: Don't Learn to Live with It - Fredericks C. (New York Grosset and Dunlap, 1981)
A distinguished food expert offers a nutritional approach to the treatment of arthritis, emphasizing the role of a proper diet in combating disease, improving vitality, and promoting health
.
Keywords: 61